Plasma Livestock Participation Level in Patterns of Broiler Partnership in West Lombok District - Muhamad Yasin; Muh. Prasetyo Nugroho (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the characteristics of plasma farmers, the level of participation of plasma farmers, and the correlation between the characteristics and the level of participation of plasma farmers in partnership pattern broiler chicken farming businesses in West Lombok Regency. Three sub-districts in West Lombok Regency, namely, Gerung Sub-district, Lingsar Sub-district and Sheet Sub-district were chosen as sample locations purposively, taking into account that there were breeders who had at least two years of experience as plasma breeders in the partnership pattern broiler chicken farming business. All plasma breeders who met these requirements, namely 18 people, were taken as respondents. Primary data collection was carried out using interviews and direct observation at the location of the farmer's farm. The collected data was analyzed using a scoring system and the Spearman Rank correlation statistical test. The results of the research show that the level of farmer participation in the partnership pattern broiler chicken farming business is classified as moderate, and the correlation of characteristics with the level of farmer participation, only the number of family dependents and the experience factor as a plasma farmer are significant (p<0.05) with a correlation coefficient (rs) -0.656 and 0.567 respectively.